Optimal Office Location Boosts Employee Performance in Indonesia - Fahril Indriyanto; Vera Firdaus (Indonesian Journal of Law and Economics Review, 2024)
This study explores the impact of organizational commitment and work engagement on employee performance, focusing on the role of office location in PT Sentosa Abadi Transport. Using a quantitative approach, data were collected from 100 employees through a questionnaire and analyzed with SPSS. The findings reveal a positive and significant relationship between organizational commitment, work engagement, and employee performance. An optimal office location enhances these factors, suggesting that management should prioritize strategic office placement and supportive work environments to boost performance and organizational effectiveness. Highlight: Positive Relationship: Organizational commitment significantly boosts employee performance. Optimal Office Location: Enhances commitment and engagement. Management Strategy: Prioritize supportive environments to improve effectiveness. Keyword: organizational commitment, work engagement, employee performance, office location, quantitative research